The Influence of Social Interaction in Language Learning and Communication Skills: A Psycholinguistic Study - fudhaili, achmad (The Progress: Journal of Language and Ethnicity, 2023)
The aim of this research is to present a broad picture of how social contact influences language acquisition and communication skills. This essay will examine many topics, such as the influence of interpersonal relationships (sociolinguistics) on language acquisition and the relationship between personal psychology and effective communication. This research uses a qualitative approach and is a literature review examining various literature on social interaction's influence on language learning and communication skills. Some of the main types of citations used are books, seminar papers, publications, print and online editions of scientific journals, research findings, and articles taken from the internet. This research shows the importance of teacher and student interaction patterns during the language learning process, which will help us better understand the importance of communication skills or stimulus responses in the learning process. This will help the educational process lead to the development of children's skills according to their needs, attitudes, and intellectual intelligence.